Boon or Bane? Trade Sanctions and the Stability of International Environmental Agreements - Achim Hagen; Jan Schneider (University of Oldenburg, Department of Economics, 2017)
In spite of scientific agreement on the negative effects of anthropogenic climate change, efforts to find cooperative solutions on the international level have been unsatisfactory so far. Trade sanctions in the form of import tariffs are one principal measure discussed as a means to foster cooperation. Former studies have concluded that import tariffs are an effective mechanism to establish international cooperation. However, most of these studies rely on the assumption that outsiders are not able to retaliate, i.e. to implement import tariffs themselves. In this paper we use combined analytical and numerical analysis to investigate implications of retaliation. We find a threshold effect: below a certain coalition size the effect of retaliation predominates and decreases incentives to be a coalition member. In coalitions above the threshold size the effect of trade sanctions that stabilizes coalitions dominates and enables the formation of larger stable coalitions. Our analysis suggests that only after a sufficiently large climate coalition has already been formed, the threat of trade sanctions might be an effective stick to establish the grand coalition.
Keywords: D58; Q54; Q58; 330; international environmental agreements; computable general equilibrium